Deutsche Version der Northoff Catatonia Rating Scale (NCRS-dv): ein validiertes Messinstrument zur Erfassung katatoner Symptome - Hirjak, Dusan; Thomann, Philipp; Kubera, Katharina Maria; Wolf, Robert Christian (Der Nervenarzt, 2017)
The clinical picture of catatonia includes impressive motor phenomena, such as rigidity, dyskinesia, festination, negativism, posturing, catalepsy, stereotypies and mannerisms, along with affective (e. g. aggression, anxiety, anhedonism or emotional lability) and behavioral symptoms (e.g. mutism, autism, excitement, echolalia or echopraxia). In English speaking countries seven catatonia rating scales have been introduced, which are widely used in clinical and scientific practice. In contrast, only one validated catatonia rating scale is available in Germany so far. In this paper, we introduce the German version of the Northoff catatonia rating scale (NCRS-dv). The original English version of the NCRS consists of 40 items describing motor (13 items), affective (12 items) and behavioral (15 items) catatonic symptoms. The NCRS shows high internal reliability (Crombachs alpha = 0.87), high interrater (r = 0.80-0.96) and high intrarater (r = 0.80-0.95) reliability. Factor analysis of the NCRS revealed four domains: affective, hyperactive or excited, hypoactive or retarded and behavior with individual eigenvalues of 8.98, 3.61, 2.98 and 2.82, respectively, which explained 21.5 %, 9.3 %, 7.6 % and 7.2 % of variance, respectively. In conclusion, the NCRS-dv represents a second validated instrument which can be used by German clinicians and scientists for the assessment of catatonic symptoms.